Prolonging shelf life of ber under semi-arid environment (Indian Journal of Arid Horticulture, 2025)
An experiment was conducted during the year 2005 and 2006 to study the effect of CaCl,, Til oil 2.0% emulsion. potassium permanganate coated silica gel @ 10 g per bag, potassium sulphate 2.0% and mustard oil 2.0% emulsion on shelf life and fruit quality attributes of ber (Zizyphus mauritiana Lam.) cv. Gola during storage at ambient temperature under semi- arid environment of western India. Different post harvest treatments were imposed to the fruits after harvest. Increase in physiological loss in weight (PLW), spoilage percentage, total soluble solids, total sugar and reducing sugar and decrease in acidity, ascorbic acid with advancement of storage period were general phenomena in all the treatments. Fruits treated with calcium chloride 1.5% recorded the least physiological loss in weight (17.45%) and spoilage loss (25.20 %) and exhibited 5 days of shelf life, while untreated control had 3 days shelf life under ambient conditions. The same treatment also showed lowest respiratory activity (0.22 mg CO, kg 'hr'), however, it was recorded highest in the control (0.43 mg CO2kg 'hr') on the last day of storage (day 9). It was closely followed by calcium chloride 2.0%. It may be concluded that the fruits treated with calcium chloride (1.5%) was found most efficient to retain the fruit quality attributes till the last day of storage under ambient conditions of western India.
Keywords: Shelf life; physiological loss in weight; poilage loss; respiration rate